التشوهات المعرفية والاضطرابات الانفعالية كمنبئات بالتسويف الأكاديمي لدى عينة من طالبات كلية التربية - جامعة نجران - أبو العنين، حنان عثمان محمد; الغامدي، رحمة علي أحمد (جامعة حائل, 2022)
هدفت الدراسة الحالية إلى التعرف على مدى انتشار التسويف الأكاديمي والتعرف على التشوهات المعرفية والاضطرابات الانفعالية التي تنبا بالتسويف الأكاديمي لدى عينة الدراسة، تم اختيار عينة الدراسة بطريقة عشوائية وتكونت من (150 طالبة) من طالبات كلية التربية جامعة نجران بقسم علم النفس من مستويات أكاديمية مختلفة، تم استخدام مقياس التشوهات المعرفية (عبد الرازق، 2015) وتم تقنينه على البيئة السعودية ومقياس الاضطرابات الانفعالية (إعداد الباحثتان) ومقياس التسويف الأكاديمي (الكفيري، 2016)، استخدمت الباحثتان المنهج الوصفي التحليلي، وقد توصلت نتائج الدراسة إلى وجود ارتباط موجب دال إحصائيا عند مستوى دلالة (0.01) بين درجات أفراد عينة الدراسة على مقياس التشوهات المعرفية ودرجاتهم على مقياس التسويف الأكاديمي، ووجود ارتباط موجب ر=0.637 <0.01 دال إحصائيا عند مستوى دلالة (0.01) بين درجات أفراد عينة الدراسة على أبعاد مقياس الاضطرابات الانفعالية (الاكتئاب، القلق، الخجل، الخوف من الفشل، والغضب) والدرجة الكلية للمقياس ودرجاتهم على مقياس التسويف الأكاديمي، كما أشارت النتائج إلى أن (الاضطرابات الانفعالية، والتشوهات المعرفية) لهما قدرة تنبؤيه بالتسويف الأكاديمي، وتوصي الدارسة بتقديم برامج إرشادية لخفض التسويف الأكاديمي لدى طلاب الجامعة. The current study aimed to identify the extent of academic procrastination and identify cognitive distortions and emotional disorders that predict academic procrastination in the study sample. The study sample was randomly selected and consisted of (150 students) from the College of Education - Najran University, Department of Psychology from different academic levels. The cognitive distortions scale was used (Abdel Razek, 2015) and it was standardized for the Saudi environment, the emotional disorders scale (The researchers) and the academic procrastination scale (Elkefiry, 2016). The researchers used descriptive and analytical approach, The results of the study concluded that there is a positive statistically significant correlation at the level of significance r= 0.6370.01 between the scores of the study sample individuals on the scale of cognitive distortions and their scores on the academic procrastination scale, and there are a positive statistically significant correlation at the level of significance (0.01) between the degrees of the study sample on the dimensions The scale of emotional disorders (depression, anxiety, shyness, fear of failure, and anger) and the overall score of the scale and their scores on the academic procrastination scale, and the results indicated that the two independent variables (emotional disorders, and cognitive distortions) have a predictive ability of academic procrastination, The study recommends providing extension programs to reduce academic procrastination among university students.
Keywords: علم النفس التربوي -- التسويف الأكاديمي -- طلبة الجامعات -- الجامعات السعودية